Removal of Methylene Blue Intensified Ozonation Using a High-Performance Rotating Reactor - Nguyen, Phuong Thao; Trinh, Minh Viet; Pham, Thi Doan; Trinh, Van Tuyen; Thi, Thom Dang; Linh, Phuong Phung; Tuan, Minh Nguyen (JST: Engineering And Technology For Sustainable Development, 2023)
The advanced oxidation processes (AOPs) were commonly used in textile dyeing wastewater treatment due to its ability to rapidly degrade dyed compounds. However, its disadvantage is the limited dispersion of ozone in wastewater. To minimize the disadvantage, it is necessary to improve the gas-liquid phase contact to maximize the dispersion of ozone in the wastewater body. Therefore, this study investigated the methylene blue (MB) treatment efficiency in textile dyeing wastewater by performing the ozonation process using a high-performance rotating reactor (HP2R) and compared it with the conventional system. The effect of basic operation parameters such as initial pH, initial methylene blue concentration (Co), rotational speed (ω), and the liquid flow rate (QL) on the decolorization efficiency (η) was evaluated. The results showed that the η of the ozonation using the HP2R reached 98% (pH 8) after only 5 minutes, which was 1.8 times higher than that (54%) of conventional ozonation at the identical period. The decolorization efficiency increased with increasing rotational speed (from 82.0 to 92.5% as ω increased from 30 to 1200 rpm), decreasing liquid flow rate (from 98.0 to 74.9% as QL increased from 0.1 to 0.4 l/min) and decreasing initial concentration of MB (from 98.0 to 88.5% as Co increased from 50 to 200 mg/l). These results show that the combined ozonation in the high-gravity technology can be widely applied to various dyeing wastewater treatment processes in general.